Performance Inquiry as Political Participation: A Storied and Embodied Model for Community Based Research - Yolanda Nieves; Randee Lipson Lawrence (Adult Education Research Conference, 2010)
This paper introduces a model of arts-based research using performance to center a sub-altern perspective utilizing a feminist process of data analysis and representation. Stories are collected from narrative interviews and then analyzed and expressed as performance text in the communities where they originated. Research becomes accessible beyond the academy while purposely centering previously marginalized voices.